Towards the Integration of Additive Manufacturing for Freeform Steel and Glass Façade Construction - Lia Tramontini (A+BE: Architecture and the Built Environment)
The dissertation ‘Towards the integration of Additive Manufacturing for Freeform Steel and Glass Façade Construction’ explores the use of Additive Manufacturing (AM) as a means of improving the design and construction of Freeform Steel and Glass Façades (FFSGF). This type of construction involves the design, fabrication, and assembly of complex components, which requires close interdisciplinary collaboration to realize the architectural vision of the designer and achieve good façade performance while also striving for efficiency in design, material use, fabrication, construction, and cost.